Implementation of Total Quality Management in Kuttab Model Islamic Education Institutions: Case Study at the Islamic Education Institution Buku Al-Fatih Bogor - Bialfino, Rio; Masyitoh, Masyitoh; Suryadi, Ahmad (Publisher Cv. Inara, 2023)
This research is motivated by the increasing trend of Indonesian people's interest in non-formal education in Indonesia. This trend of increasing public interest in the Kuttab model of Islamic Education needs to be maintained and continuously improved. This research aims to implement Total Quality Management at Kuttab Al-Fatih Islamic Education Institution. This research uses qualitative research, namely field research and literature research. The research informants comprised the head of Kuttab, Kuttab educators, Kuttab document observation, and Kuttab activity observation. The research findings show that the implementation of TQM at Kuttab Al-Fatih Islamic Education Institution is based on School Self Evaluation of 8 national education standards, which include components of Graduate Competency Standards, Process Standards, Assessment Standards, Graduate Competency Standards, Content Standards, Educational Facilities and Infrastructure Standards and Education Personnel adapted from the Al-Quran, Sunnah, and Siroh based on the ulama book. In addition, the management of Kuttab Al-Fatih Bogor has implemented TQM principles from 4 TQM Teachers, namely Demings, Sallis, Crosby, and Juran, although there are still some things that must be improved. In addition, some supporting and inhibiting factors for TQM implementation were also found.